Hypothetical Preferences and Concerns for Long-Acting Injectable HIV PrEP Use Among Female Barmaids in Ubungo, Dar Es Salaam, Tanzania - Akyoo WO; Mosha IH; Mpembeni RM; Jahn A (HIV/AIDS: Research and Palliative Care)
Winfrida Onesmo Akyoo,1,2 Idda Hubert Mosha,1 Rose Msuya Mpembeni,3 Albrecht Jahn2 1Department of Behavioural Sciences, School of Public Health and Social Sciences, Muhimbili University of Health and Allied Sciences, Dar Es Salaam, Tanzania; 2Heidelberg Institute of Global Health, University of Heidelberg, Heidelberg, Germany; 3Department of Epidemiology and Biostatistics, School of Public Health and Social Sciences, Muhimbili University of Health and Allied Sciences, Dar Es Salaam, TanzaniaCorrespondence: Winfrida Onesmo Akyoo, Email akybless@gmail.com; akyoo.winfrida@uni-heidelberg.deBackground: Oral HIV pre-exposure prophylaxis (PrEP) has been introduced globally, but women in sub-Saharan Africa frequently experience challenges in uptake and adherence. Female barmaids are at HIV risk due to transactional sex. However, uptake and adherence to oral PrEP pills is poor. Long-acting injectable (LAI) PrEP has the potential to increase prevention by improving adherence. Nevertheless, LAI PrEP is yet to be initiated in Tanzania. We explored preferences and concerns about LAI PrEP use among female barmaids in Ubungo municipality.Methods: We conducted in-depth interviews with 17 purposefully selected female barmaids. Interviews were conducted using a guide with semi-structured questions. We adopted an inductive approach for analyzing data.Findings: The majority of PrEP non-users expressed no preference for any form of PrEP, while oral PrEP-users preferred LAI PrEP. Overall, LAI PrEP was preferred due to its discretion, fewer side effects, prolonged prevention, and reduced fatigue compared to oral pill PrEP with concerns about large pill size, side effects, and the burden of daily use. Most interviewees indicated a three-month PrEP injection preference, though some preferred a monthly PrEP injection for effective monitoring and control of potential side effects. Regarding the delivery model, the healthcare facility was mostly preferred for timely services, convenience more privacy and reduced stigma. Community spots were preferred for convenience and friendlier services from providers. The majority reported no major concerns about using LAI PrEP, though a few expressed concerns about its trial phase, potential links to cancer, risky sexual behaviours, and side effects such as fatigue, dizziness.Conclusion: The majority of the interviewees expressed strong interest in LAI PrEP and reported fewer concerns, emphasizing more convenience and discretion. Our findings suggest that since LAI can address challenges of adherence associated with daily PrEP pills, it is important to introduce it to expand HIV prevention options for barmaids and other women at risk of HIV in Tanzania.Keywords: long-acting injectable PrEP, preferences, concerns, female barmaids